2018
DOI: 10.1007/s41465-018-0103-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dancing on Cognition in Healthy Older Adults: a Systematic Review

Abstract: A growing body of research emphasizes the benefits of physical activity and exercise over the lifespan and especially in elderly populations. However, few studies have evaluated the impact of dance as a physical activity or exercise on cognition in healthy older adults. This review investigated if dance could be used as a promising alternative intervention to address physical inactivity and to cognitively stimulate older adults. This systematic review reports the effects of dancing in a healthy older adult pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 39 publications
2
40
0
2
Order By: Relevance
“…Therefore, a dance training consisting of complex sensorimotor, rhythmic, and physical activity integrating multiple cognitive and social elements ( 30 32 ) combined with a coordinative–cognitive demanding training could have superior effects on designated cognitive functions, leading to a decreased gait variability. Several studies already applied dancing interventions in elderly with and without mild cognitive impairment, indicating an improvement in cognitive functions ( 25 , 33 , 34 ). These multiple improvements especially the reduction in gait variability could lead to a reduced risk of trip-related falls in people with chronic LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a dance training consisting of complex sensorimotor, rhythmic, and physical activity integrating multiple cognitive and social elements ( 30 32 ) combined with a coordinative–cognitive demanding training could have superior effects on designated cognitive functions, leading to a decreased gait variability. Several studies already applied dancing interventions in elderly with and without mild cognitive impairment, indicating an improvement in cognitive functions ( 25 , 33 , 34 ). These multiple improvements especially the reduction in gait variability could lead to a reduced risk of trip-related falls in people with chronic LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Verghese et al [65] maintain that people who dance four times a week might reduce the risk of dementia by 76%. These findings have been also supported by Predovan et al [52] whose review suggested that dance can be used as a promising alternative intervention to address physical inactivity and to cognitively stimulate older adults. In addition, it can positively affect older people's mood by its socializing effect [66], which is superior to all other forms of the mentioned physical activities.…”
Section: Discussionmentioning
confidence: 53%
“… The primary outcome did not focus on the effect of the physical activity on cognitive functions among the healthy elderly [ 45 , 46 ]. Study protocols [ 47 , 48 ], cross-sectional studies, e.g., [ 4 ], prospective cohort studies [ 20 ], and review studies, e.g., [ 6 , 32 , 49 , 50 , 51 , 52 ] were also excluded. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third year of Journal of Cognitive Enhancement (2019) included a broad overview of theory-driven cognitive enhancing articles ranging from cognitive training for military application (Blacker et al 2019), a new perspective suggesting that embodied cognition represents a productive framework to explain results and to inform new studies aimed at enhancing cognition (Zona et al, 2019), the enhancing effects of dancing on cognition in aging (Predovan et al, 2019), the drawbacks of meditation practice (Anderson et al, 2019), and the potential negative effects of brain stimulation for cognitive enhancement (Krause et al, 2019).…”
mentioning
confidence: 99%